Implementasi Pendidikan Inklusif di SD Negeri Unggulan Mongisidi I: Penelitian - Fadyla Nur Aprilia; Ahlun Ansar; Putri Ekayanti; Wahid Ramadha; Arismunandar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Inclusive education represents an effort to provide equal learning opportunities for all children, including those with special needs; however, its implementation at the elementary school level still faces various challenges such as limited facilities, insufficient teaching staff, and a lack of environmental support. This study aims to describe the implementation of inclusive education at UPT SPF SD Negeri Unggulan Mongisidi I, covering aspects of school policy, learning implementation, the roles of teachers and parents, as well as the challenges encountered. Using a qualitative descriptive approach with data collected through observation, interviews, and documentation, the findings indicate that the school has implemented inclusive education policies effectively through the application of equality principles, a modified curriculum, and collaboration among teachers, the principal, and parents. The school has also provided several supporting facilities such as ramps and simple learning aids, although there remain limitations in human resources and physical infrastructure. Regular evaluations are carried out to assess student progress and learning effectiveness. In conclusion, the implementation of inclusive education at SD Negeri Unggulan Mongisidi I reflects a strong commitment to creating a fair, inclusive, and friendly learning environment for all students.